HORMONE-GENETIC MECHANISMS OF METABOLIC-RELATED FATTY LIVER DISEASE IN WOMEN OF REPRODUCTIVE AGE. LITERATURE REVIEW (Multidisciplinary Journal of Science and Technology, 2026)
Metabolic fatty liver disease is one of the most pressing problems of modern hepatology and metabolic medicine. In addition to insulin resistance, visceral obesity, dyslipidemia, and chronic low-grade inflammation, hormonal imbalance and genetic factors also play an important role in the formation of this disease. Especially in women of reproductive age, genes related to estrogens, androgens, sex hormone binding globulin, the aromatase system, and steroid metabolism are inextricably linked to hepatic steatosis and its stages of exacerbation. This literature review analyzes the modern definition of metabolic fatty liver disease, hormonal characteristics observed in women, its association with polycystic ovary syndrome, the possible pathogenetic role of genes such as SHBG, CYP19A1, UGT2B15, and UGT2B17, and promising scientific directions. The available data indicate the need for a comprehensive study of not only anthropometric and biochemical indicators, but also hormonal-genetic markers in the assessment of this disease in women of reproductive age.